Synthesis of highly functionalized 1, 6-dihydropyridines via the Zn(OTf)2-catalyzed three-component cascade reaction of aldimines and two alkynes (IA2-coupling). Issue 17 (17th April 2018) - Shehzadi, Syeda Aaliya; Vande Velde, Christophe M. L.; Saeed, Aamer; Abbaspour Tehrani, Kourosch
Abstract : One pot Zn(ii )-catalyzed imine–alkyne–alkyne coupling. Abstract : A zinc(ii ) triflate catalyzed three component synthesis of 1, 6-dihydropyridines, involving aldimines, alkynes and electron-deficient dimethyl acetylenedicarboxylate (DMAD), in good to excellent yields has been described. Besides a range of different N -substituents, a variety of both aromatic and aliphatic alkynes could be used. The application of electron-deficient propiolates instead of DMAD resulted in regiospecific incorporation of the ester functionality on the 1, 6-dihydropyridine ring. The reaction proceeds via a cascade reaction involving nucleophilic addition of the metal acetylide to the imine, followed by the addition of the intermediately formed propargylic amine to the electron-deficient alkyne and subsequent 6- endo dig cyclization.